Is There Enough Effort by Corporations in Malaysia to Promote Ethical Leadership and Long-Term Growth? A Perspective Analysis - Anantha Raj A. Arokiasamy; Alice Tamah (Inclusive Society and Sustainability Studies, 2021)
Employees are under greater pressure to tackle more difficult ethical issues as global competition and economic demands rise. It focuses on the concept of ethical leadership, the personality traits of ethical leaders, and the views linked to the antecedents and results of ethical leadership. Following an ethical approach leads in a positive experience for everyone involved in a firm; the issue of ethical leadership is discussed in this article. Ethical leadership is a form of leadership in which individuals act in ways that are acceptable and essential for the greater good in all parts of their lives. Any individual in a management position should exercise ethical leadership. This is the most major ethical problem that our society and workplace confront, as well as the most significant ethical leadership task. This study provides possibilities for academics to investigate new findings in leadership style and aids in understanding how companies may produce ethical leaders in the workplace. A successful and efficient leader blends ethics and leadership, making their presence known and emerging as a role model to play a more positive and important role in a company. The presentation also addresses the subject of developing ethical leaders for the twenty-first century. One of the goals of university education is to develop students' common sense so that they may become effective citizens who can contribute constructively to our community and industry. This guarantees that teachers in charge of ethics curriculum and preparation in companies must ensure that future leaders grasp the ideas and implement ethical standards in their everyday job routines.